Feeding the future's changing diets: Implications for agricultural markets, nutrition, and policy - Rosegrant, Mark W.; Msangi, Siwa (International Food Policy Research Institute, 2011)
This paper explores the nature of several key drivers of change in food systems and examines a number possible entry points for policy intervention to determine their effect on food prices and other market-driven outcomes. Among the drivers of change discussed are those of diet change, which is an important demand-side driver for the longer-term evolution of agricultural market dynamics. We demonstrate the nutrition-enhancing effects that occur when meat consumption, production, and feed demand is decreased, and argue that further benefits ensue when this is supplemented with higher intakes of pulses fruits and vegetables under a “healthier” diet regime. We use a global supply, demand, and trade model to simulate these effects out to 2030 to illustrate the implications for various world regions embodying different rates of socioeconomic and demographic change. We also discuss the implications of our scenarios within the policy design context, and contrast the ability of policy to handle shorter-term issues through direct intervention against those pathways that might be effective in promoting longer-term health and safety outcomes for consumers.